THE IMPLEMENTATION OF ONLINE LEARNING ACTIVITIES DURING COVID-19 OUTBREAK - Wijaya, Kristian Florensio (Jurnal Penelitian Humaniora, 2024)
This library study sought to investigate the implementation of online learning activities during the Covid-19 outbreak. To increase the reliability, robustness, and comprehensibility forming in this small-scale library study, the researcher employed a thematic analysis while clustering the most identical research findings from 30 previous online learning activity studies into some thematically categorized themes. As the topmost prioritization of this small-scale library investigation was to generate more comprehensible, relatable, and applicable research results beneficial for the betterment of worldwide English language teaching-learning enterprises, the researcher selected 30 published online learning activity investigations uploaded in varied journal article platforms ranging from 2020 to the 2022 year. Based on the data agglomeration final results, online learning activities promoted various advantages and disadvantages concerning EFL learners’ target language proficiency levels advancement and habitual classroom learning vicinities. Anchoring on this unassailable fact, globalized educational institutions and second language educators should work hand-in-hand to invent more contextual online learning dynamics currently matching with nowadays EFL learners’ learning needs, skills, and preferences.